Ventral Striatum Dopamine D2 Receptor Activity Inhibits Rat Pups’ Vocalization Response to Loss of Maternal Contact - Muller, Jeff M. (2008)
Most mammalian infants vocalize when isolated. The vocalization promotes caregiver proximity, which is critical to survival. If, before isolation, a rat pup has contact with its dam, its isolation vocalization rate is increased (maternal potentiation) relative to isolation preceded only by littermate contact. Prior work showed that systemic administration of a D2 receptor agonist blocks maternal potentiation at doses that do not alter baseline vocalization. In this study, infusion of quinpirole (2 µg/side) into the nucleus accumbens also blocks maternal potentiation. Infusion of the accumbens with the D2 antagonist raclopride (4 µg/side) prevents systemic quinpirole from blocking potentiation. Quinpirole infusion in the dorsal striatum did not affect maternal potentiation and infusion of raclopride in the dorsal striatum did not reverse the block of maternal potentiation by systemic quinpirole. Vocalization results after a second vehicle infusion on a given day are no different than the results following an initial vehicle infusion, so experimental design can not account for the effects of drug infusions. Because activity level was increased by both dorsal and ventral striatum infusions, activity level can not account for the results.